Analisis Prediksi Kebangkrutan Menggunakan Model Altman Z-Score Pada Perusahaan Makanan Dan Minuman (Studi Kasus Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2014) - Jevri, Muhammad, Nur achmad, SE, M.Si (2016)
The purpose of this research is to predict the bankruptcy on food and beverage companies were listed on the Indonesia stock exchange period 2012-2014. Food and beverage companies was chosen because the industrial sector continues to undergo development in developed and developing countries one of them in Indonesia. Sampling techniques in the study using a Purposive Sampling and random sampling so that the sample used in this study there are 10 food and beverage companies. Technique of data analysis used the bankruptcy prediction model of Altman Z-score. By using five variables that represent the ratio of the liquidity of the x 1, x 2 and X 3 activity Profitability X 4 and x 5. With the Z-score formula = 1.2 X1 + 1,4 X2 + 3,3 X 3 + 0,6 X 4 + 1,0 X 5. With the assessment criteria of the Z-score > 2.99 categorized as a healthy company. 1,81 < Z-score < 2,99 categorized as companies that are in the grey area and so the possibility of survivors and likely bankrupt the same magnitude depends on the discretion of the company management's decision as decision makers. Z-score < 1,81 categorized as a company that has a huge financial difficulties so that the possibility of the company went bankrupt. Based on the results of a calculation that was done then it can be summed up food and beverage companies are experiencing a fluctuating financial conditions annually and an average healthy conditions. The year 2012, 10% of the company's predicted bankruptcy, 70% are in a healthy condition and 20% brada on grey areas. By 2013, a company that is in a healthy condition to decline to 60%, grey area is increased to 30% and 10% of bankrupt condition. By 2014, the company that is in a healthy condition to climb back to 70%, grey area remain 30% and the company is in bankrupt 0%, meaning that there is no company that is in insolvent in 2014. Keywords: Altman Z-score, financial difficulties, bankruptcy Prediction.